Green building occupants' social dimensions in the post occupancy stage - empirical findings / Siti Nurul Ainun Mohd Mustafa, Natasha Khalil and Asmah Alia Mohamad Bohari - Mohd Mustafa, Siti Nurul Ainun; Khalil, Natasha; Mohamad Bohari, Asmah Alia (2022)
In the past few decades, scholars have extensively conducted research and held discussions on the sustainable development to elevate the awareness of mitigating environmental problems. Sustainability initiatives have been developed in addressing not only for the environment, but also to the economic and social concerns. In construction, green building substantiates the sustainable development concept when it's designed to balance the environment, economic, and social needs of its occupants. Hence, it is crucial to sustain the green building impacts, not only at the pre-construction stage, but later the post occupancy stage which has the longest period. Nevertheless, amongst of all three sustainability factors, little attention is focused on the social dimensions which include the occupant's comfort and health perception of green buildings. It's even more concerning when many recent studies show discrepancies of occupants' satisfaction in providing better comfort and health in residing green buildings. Therefore, this paper provides the empirical findings on the concept of social needs in providing comfort and health to the occupants and to explore the social factors in green building performance evaluation in post occupancy stage. Eventually, by identifying the social needs of occupants with regards to comfort and health will aid the designers to understand sustainable parameters perceived as important as ones that utilize and reside the building.